Respuesta :
15 + x = 19 - 45
15 + x = -26
15 - 15 + x = -26 - 15
x = -41
Explanation:
write it as an algebraic expression
simplify the right side of the equation
then you should subtract fifteen from both sides -15
x should equal -41
15 + x = -26
15 - 15 + x = -26 - 15
x = -41
Explanation:
write it as an algebraic expression
simplify the right side of the equation
then you should subtract fifteen from both sides -15
x should equal -41
it is -11 because when u get the expression which is 15+x=-26 15 becomes -15 and you subtract -26 and -15 and u will get -11